P4.003 The complexity of supervision: impact of parental supervision style on children's risk-taking. (14th March 2021) - Morgan, Casie; Estep, Claire; Bullard, Caitlin; Cangialosi, Brittany; Schwebel, David
Abstract : Background: Active supervision to prevent child injury encompasses close proximity, full attention, and continuous monitoring (Saluja et al, 2004). Absent components may increase injury risk. We examined the impact of supervision and supervision styles on children's risk-taking. Methods: 59 children aged 4–6 years (Mage=5.47, SD=.47) engaged in an activity room with hazards (e.g., ball pit) for ten minutes (supervised, then unsupervised). Parents completed questionnaires while 'supervising, ' creating poor attention/non-continuous monitoring. Children also responded to 12 illustrated risk-taking activities (6 pairs, split between unsupervised/actively supervised), indicating preferred engagement in risks. To assess supervision style, parents completed the PSAPQ (Morrongiello & House, 2004), which includes four scales: supervision (keep close watch), protectiveness (strong sense of responsibility), fate (injuries are bad luck; excluded from analyses given focus), and risk-tolerance (encourage independence). Results: Activity Room: Children took similar risks when supervised (.34±.27) and unsupervised (.30±.24), t(59)=-1.10. Bivariate correlations revealed greater risk-taking with more protective/supervision-oriented parents. Multiple linear regression predicting supervised play from PSAPQ scales was significant, F(3, 53)=4.90, p<.05, R²=.22; only protectiveness significantly predicted, p<.05. Illustrations: Children took fewer risks when supervised (2.29±1.55) than unsupervised (1.80±1.71), t(59)=2.81, p<.05. Bivariate correlations revealed greater risk-taking for more supervision-oriented parents. Multiple linear regression predicting supervised risk-taking from PSAPQ scales was non-significant, F(3, 54)=2.56, p=.07, R²=.13, although supervision significantly predicted, p<.05. Conclusion: These findings support crucialness of active parental supervision for child injury prevention, and safe risk-involved exploration for child development. Inattentive supervision may increase risk. Learning Outcomes: Parental supervision quality and type impacts children's risk-taking.